2020
DOI: 10.1186/s13099-020-00350-z
|View full text |Cite
|
Sign up to set email alerts
|

Complete genome of Enterobacter sichuanensis strain SGAir0282 isolated from air in Singapore

Abstract: Background: Enterobacter cloacae complex (ECC) bacteria, such as E. cloacae, E. sichuanensis, E. kobei, and E. roggenkampii, have been emerging as nosocomial pathogens. Many strains isolated from medical clinics were found to be resistant to antibiotics, and in the worst cases, acquired multidrug resistance. We present the whole genome sequence of SGAir0282, isolated from the outdoor air in Singapore, and its relevance to other ECC bacteria by in silico genomic analysis. Results: Complete genome assembly of E.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…It is an opportunistic pathogen that can cause nosocomial infections, urinary tract respiratory, ear, digestive, and wound infections, burns, and otitis media (Al-Mayahi, 2017). Uchida et al (2020Milstone et al, 2004 Enterobacter sp can be found on the human skin, plants, soil, water, sewage, and intestinal tracts of man and animals. They are considered opportunistic pathogens, rarely causing disease in healthy individuals, but associated with infections in immune-compromised individuals.…”
Section: Discussionmentioning
confidence: 99%
“…It is an opportunistic pathogen that can cause nosocomial infections, urinary tract respiratory, ear, digestive, and wound infections, burns, and otitis media (Al-Mayahi, 2017). Uchida et al (2020Milstone et al, 2004 Enterobacter sp can be found on the human skin, plants, soil, water, sewage, and intestinal tracts of man and animals. They are considered opportunistic pathogens, rarely causing disease in healthy individuals, but associated with infections in immune-compromised individuals.…”
Section: Discussionmentioning
confidence: 99%